UNIQUE COLLECTIONS OF VENDOBIONTES AT GEOLOGICAL MUSEUM OF NATIONAL MUSEUM OF NATURAL HISTORY (NMNH), NAS OF UKRAINE - Grytsenko, V.; Palij, V.; Derevska, K.; Rudenko, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Investigations of of Vendian sections of Podillia have brouhg new achievements and discoveries. The collections of Vendian biota, studied by many researchers are stoted in museums and private collections. Practical importance of these investigation is the possibility to do paleothological substantiation of stcratigraphic schemes and obtaining of reliable reasons for correlation of deposits. As result of many years’ expeditions, the collections of Vendian lithological, mineralogical and paleontological samples from Middle Dniester area were gathered. In particular, rich representative materials were sampled during repeated field trips to Novodnistrovsk area that are made for studying and monitoring of sections of Mogyliv and Yaryshiv Suites outcropped in Bernashivka open pit. Both early known and new genera and species of Vendian fossil organisms were found here.Prolonged investigation of certain levels in the section has allowed us to trace facial-lithological features of layers and alterations in horizonts which contain findings of vendobiontes. Presence of various cyclic and bilateral symmetry of fossils and traces of their vital activity allows us to correlate Vendian sediments of Podillia and coastal area of White Sea with Ediacaran sediments (Late Proterozoic) of Australia and other continents. A large international importance of the section their paleonthological, geological and biological diversitis form basis fro for creation of a new natural conservation object at the base of the open pit. For conservation of Vendian geological sections in Middle Dniester area we propose to give them in step-by-step manner possible environmental status with declaring them as nature geological monuments with the possibility of scientific sampling for doing more detailed study of unique Vendian biota. The activity should be started from Bernashivka open pit.